Water in textiles and fashion consumption, footprint, and life cycle assessment - Muthu, Subramanian Senthilkannan (Woodhead Publishing, 2019)
"Water in Textiles and Apparel: Consumption, Footprint, and Life Cycle Assessment provides a thorough analysis of one of the most urgent issues facing the textiles industry. As water is essential to the textile production system, and as availability of water is reduced due to natural and anthropogenic factors, the industry must consider its response.